Evaluating the Bank Queuing Systems by Fuzzy Logic - Halil KILIF; Ilker Ali OZKAN (International Journal of Applied Methods in Electronics and Computers, 2020)
Various models are used in the banking system to organize the queue structure of customers’ banking transactions. The average waiting time for a customer in the queue generally varies depending on whether bank customer or not and the customer score it has. Different uncertain parameters are used to determine the individual queue group and average waiting time in bank queuing systems. This paper proposes a fuzzy logic-based approach in bank queuing systems. In this study, individual bank queue group and average waiting times are determined according to the number of waiting customers, customer score and credit score parameters. In addition, identification number is a determining factor for the priority of transactions in bank queuing systems. People who are not customers of the bank often have longer waiting times. As a new approach to the working structure of bank queuing systems, this study also suggests that non-bank customers should be given priority sequence numbers according to their credit scores.